Prevalencia de neumonía en niñas y niños menores de 10 años atendidos en el servicio emergencia del hospital provincial general Julius Doepfner De Zamora. año 2015 - Kayap Sharian, Miriam Lorena (2016)
The following research has a purpose to determine the prevalence of pneumonia in children under 10 years old. They were treated in the emergency area at “Julios Doepfner” general Provincial hospital in Zamora city. It corresponds to the 2015 year. The type of research was observational, cross-sectional retrospective, descriptive and bibliographic. The survey and direct observation techniques were used. In order to have successful results instruments as the questionnaire and observation guide were taken. Therefore, the results were: the prevalence of pneumonia in children was 13.69% the age, which predominated, was from 1 to 5 years old with the 55.05 %. Male with 63.30 % and mixed ethnicity with 54, 13 %. Also in the rural living with 73.39 %. The type of pneumonia unspecified with 67.89 %. The factors that trigger pneumonia were incomplete secondary education of the mother with a 33.94 %. Medium- low economic level with 43.12 %. The 21.1% are overcrowded. A low birth weight with 8.26%. Breastfeeding 64.22 % incomplete and exclusive breastfeeding complete 35.79%. Incomplete vaccines 0.92%. The mother under 20 years 48.63 %. Lack of information about the causes, which causes pneumonia by an average of 51.38 %, and lack of care 49.77 %. An intervention plan was developed with an educational program. It had workshops, conferences and home visits to mothers of children. Some brochures and leaflets were given. As a conclusion, the prevalence of pneumonia is 13.69 % and the triggering factor is the lack of information about the causes of pneumonia and its care.